Analysis of the Use of AI Technology in Personalizing the Consumer Experience in Digital Marketing: A Review from Perspective - Tompo, Ismaila (Journal of Entrepreneur, Business and Management, 2024)
The utilization of Artificial Intelligence (AI) technology has become a primary subject in digital marketing strategies, particularly in efforts to tailor consumer experiences personally. This research aims to analyze in-depth literature related to the utilization of AI technology in the context of personalized customer experiences in digital marketing. The research method consists of systematic review and detailed analysis of various journal articles, books, and other literature sources related to the theme. Literature search is conducted through academic databases, including Google Scholar and Scopus, following pre-established inclusion and exclusion criteria to determine relevance to the research focus. The results of the analysis present various perspectives regarding the use of AI technology in efforts to enhance customer experiences, including the application of methods, types of technology used, challenges faced, and their impact on customer engagement and overall performance in digital marketing. This literature review also identifies significant trends, crucial findings, and knowledge gaps that may become subjects of future research. The implications of these findings provide profound insights into the role of AI technology in advancing digital marketing practices, emphasizing the importance of personalization in creating satisfying and effective customer experiences. This research is expected to make a significant contribution to the development of theory and practice in the field of digital marketing, as well as to serve as a guide for further research efforts to be undertaken.Keywords: Artificial intelligence, Personalization, Customer experience, Digital marketing.